An assessment of the financial sustainability of savings and credit cooperative societies in Kenya - Waweru, Gabriel (Research of GSB, 2018)
Savings and Credit Cooperative Societies (SACCOs) are voluntary associations of people with the common goal of encouraging savings and granting credit to members as a means to their economic improvement. For a long period of time, SACCOs have been seen as a way of ensuring savings and investments, especially by the middle and lower economic classes. In Kenya, these institutions have managed to accumulate funds running into billions of shillings, and many members have benefited from them. However, in the last few years, many of these institutions have experienced serious financial challenges that have led to some of them winding up or becoming dormant, resulting in a loss of funds for members. The primary objective of this study was to determine the factors that influence the financial sustainability of SACCOs in Kenya. The study explored the influence of financial outreach, financial regulation, corporate governance, size and age on financial sustainability. A sample of 166 SACCOs was drawn for the study, and generalised least square technique was used to analyse the data. Empirical findings of the study reveal that financial outreach, as measured by the number of members, exerts a significant influence on financial sustainability. Similarly, financial regulation, SACCOs' governance, SACCOs' size and SACCOs' age were found to exert a significant influence on the financial sustainability of SACCOs. The study has contributed to theory by applying both monetary and non-monetary measures to profitability theory of financial sustainability. While contributing to empirics, the study has delineated the relationship between the study factors and their financial sustainability status (FSS), as well as documenting the FSS of SACCOs in Kenya. In terms of methodology, the study applied the GLS analysis technique. Finally, the study provides useful information to SACCO policy makers and opens avenues for future research, thus contributing to practice. The recommendations of the study provide insights into how to rescue ailing SACCOs in Kenya and ameliorate the existing situation.